STANDARDIZATION OF SECONDARY METABOLITES AND HEAVY METAL CONTAMINATION ASSAY ON ONCHIDIID SLUG (ONCHIDIUM TYPHAE) WEST KALIMANTAN WATERS - Bambang Wijianto; Annisa Larasati Nurhidayah; Sri Luliana (Jurnal Farmasi Sains dan Praktis, 2022)
Onchidiid slug or Onchidium typhae is a marine animal commonly found in West Kalimantan waters. This gastropod is commonly used as medicine and cosmetic by the locals. This research aims to assure the content and quality of O. typhae methanol extract by determining its secondary metabolites and heavy metal contamination. Phytochemical screening of alkaloid, steroid/ triterpenoid, flavonoid, tannin, and saponin are done using reagent tests. Chromatography profile was completed using silica gel G60 F254 plate and hexane: ethyl acetate: methanol as mobile phase. Heavy metal contamination analysis was performed using atomic absorption spectrophotometry to determine Hg, As, Cd, and Pb content. The phytochemical screening and chromatography profile of O. typhae methanol extract confirm the presence of alkaloids and steroids. Heavy metal analysis stated Hg, As, Cd, and Pb content in O. typhae are < 0,0008; < 0,001; < 0,001; and 0,05 ppm respectively. Since heavy metal levels are below the maximum contamination limit, it qualifies as a natural product ingredient.